Data from: Opposing effects of mortality factors on progeny operational sex ratio may thwart adaptive manipulation of primary sex ratio - Moreau, Gaétan; Eveleigh, Eldon S.; Lucarotti, Christopher J.; Morin, Benoit; Quiring, Dan T. (Data Archiving and Networked Services (DANS), 2018)
Despite extensive research on mechanisms generating biases in sex ratios, the capacity of natural enemies to shift or further skew operational sex ratios following sex allocation and parental care remains largely unstudied in natural populations. Male cocoons of the sawfly Neodiprion abietis (Hymenoptera: Diprionidae) are consistently smaller than those of females, with very little overlap, and thus, we were able to use cocoon size to sex cocoons. We studied three consecutive cohorts of N. abietis in six forest stands to detect cocoon volume-associated biases in the attack of predators, pathogens, and parasitoids and examine how the combined effect of natural enemies shapes the realized operational sex ratio. Neodiprion abietis mortality during the cocoon stage was sex-biased, being 1.6 times greater for males than females. Greater net mortality in males occurred because male-biased mortality caused by a pteromalid parasitic wasp and a baculovirus was greater and more skewed than female-biased mortality caused by ichneumonid parasitic wasps. Variation in the susceptibility of each sex to each family of parasitoids was associated with differences in size and life histories of male and female hosts. A simulation based on the data indicated that shifts in the nature of differential mortality have different effects on the sex ratio and fitness of survivors. Because previous work has indicated that reduced host plant foliage quality induces female-biased mortality in this species, bottom-up and top-down factors acting on populations can affect operational sex ratios in similar or opposite ways. Shifts in ecological conditions therefore have the potential to alter progeny fitness and produce extreme sex ratio skews, even in the absence of unbalanced sex allocation. This would limit the capacity of females to anticipate the operational sex ratio and reliably predict the reproductive success of each gender at sex allocation. Morphological measurements of N. abietis cocoonsFate and volume (in cubic millimeters) of ...